The Advantages and Challenges of e-Learning During COVID-19 Pandemic in Omani Schools from Parents’ Perspectives of Cycle Two Schools (5-9) - Hadhrami, Shaikha Al; Saadi, Najlaa Al (International Journal of Educational Technology and Learning, 2021)
This paper aimed to investigate parents’ perspectives regarding the advantages and challenges of e-leaning faced them during follow-up their children’s learning through the e-learning platforms of the Ministry of Education in Sultanate of Oman. Target: students’ parents in Al Batinah South Governmental schools. Data were collected from 346 parents through online questionnaire taking random samples of parents. The questionnaire measured the parent’s perspectives about e-leaning advantages and challenges. The study revealed that the students’ parents were interested in using e-learning for their children, for example, the e-learning helps their children to use modern educational programs and the constant access to the recorded videos of the daily lessons effortlessly. Yet, it explored some obstacles faced them during following their children in e- learning, such as the technical challenges faced them related to limitations of network and logistical challenges related to the difficulty of time management. The collected data were analysed, and accordingly the recommendations were forwarded to be applied for future strategies and policies of e-learning in Omani schools.